Association between traffic related air pollution exposure and direct health care costs in Northern California. (15th October 2022) - Alexeeff, Stacey E.; Roy, Ananya; Shan, Jun; Ray, G. Thomas; Quesenberry, Charles Q.; Apte, Joshua; Portier, Christopher J.; Van Den Eeden, Stephen K.
Abstract: Background: Traffic related air pollution (TRAP) is associated with a complex and diverse array of health effects. It is unknown whether these effects may be reflected by higher health care costs. Objectives: Evaluate the association between TRAP exposure and direct health care costs in an elderly population. Methods: This multi-ethnic population-based cohort of 25, 684 elderly subjects, served by Kaiser Permanente Northern California (KPNC), were followed between 2013 and 2017. Hyperlocal long-term pollutant concentrations for nitrogen dioxide [NO2 ], nitric oxide [NO], and black carbon [BC] were measured at a resolution of 30 m using repeated street-level mobile measurements and linked to residential addresses. Health care utilization and costs were derived from KPNC databases and were used to calculate individual annual total health care, inpatient, outpatient, and emergency room (ER) and pharmacy costs. The associations between TRAP exposures and health care costs were evaluated using generalized estimating equation models adjusted for age, sex, race, BMI, smoking, SES and comorbidities. Subgroup analyses and interaction models were used to assess differences among specific susceptible population subgroups. Results: An IQR difference (10.1 ppb vs 4.2 ppb) in NO2 concentration was associated with a 3% (95% CI: -1%, 6%), 22% (95% CI:11%, 35%), and 5% (95% CI:1%, 8%) increase in annual total health care, ER and outpatient costs in the baseline model. Associations with black carbon showed similar patterns but were smaller in magnitude. Among those with cardiovascular diseases, an IQR increase in NO2 was associated with a 7% (95% CI: 1%, 13%) increase in total annual health care cost and 23% (95% CI: 17%, 29%) increase in ER costs. Discussion: Higher long-term TRAP exposure was associated with higher direct annual health care cost in this elderly cohort. Those with existing cardiovascular disease had particularly strong associations between TRAP exposure and direct annual health care costs. Highlights: Traffic related air pollution was associated with health care costs. The strongest associations were between nitrogen dioxide and emergency room costs. Effects were more pronounced among those with existing cardiovascular disease.